GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALITAS GURU - Erwin Junaidi, (UNISAN JURNAL, 2024)
Every student in the education unit has the right to receive religious education in accordance with the religion he adheres to and taught by educators of the same religion, so that religious education is a mandatory curriculum that must be carried out by schools from elementary to tertiary levels. The presence of PAI supervisors tends to be purely administrative and inspection with a very minimal number of visits. This is very influential on increasing the professionalism of PAI teachers at SMPN 25 Bandar Lampung , so it is not surprising that there are still many PAI teachers who are not yet professional in carrying out their duties. This is inseparable from the responsibility of the PAI Supervisor in carrying out its function as a coach, mentor, and professional developer of PAI teachers who are under his guidance. Thus, proper coaching and mentoring is needed in increasing teacher professionalism related to the function of PAI supervisors in fostering, guiding and developing the PAI teacher profession so that the problems faced by PAI teachers can be resolved. This study uses a qualitative research approach. The results of this study indicate that the results of the supervisor's performance show that it is quite good so that it is proven by the completeness of the document file. Furthermore, PAI teachers have been trained regularly by Islamic Religious Education supervisors.